(untitled) (Communication & Society, 2021)
This article explores the way Basque language cinema is adapting to streaming platforms, focusing on the case of the three Basque language films that have made it to Netflix: Loreak (2014), Handia (2017) and Errementari (2018). Firstly, it explains Netflix particularities and its emphasis on diversity, among other reasons that could explain the platform’s interest in these particular films. Secondly, it describes the way these aforementioned films have landed on Netflix and the impact this exhibition has had. I base my research on in-depth interviews with directors Jon Garaño and Paul Urkijo as well as producer Xabi Berzosa to know the insights of the process. More broadly, the article discusses the impact that becoming available on Netflix and other SVOD platforms might have for Basque cinema, especially when it comes to production and transnational distribution. On the other hand, I will also point at the challenges that this new landscape poses for the Basque audiovisual industry, and non-hegemonic languages in general. The streaming revolution, of which Netflix is currently the epitome, is changing the production, distribution, exhibition and consumption model globally, and policy makers and Basque institutions should take this transformation seriously. Loreak, Handia and Errementari should not just become happy exceptions.